Developing a WebGIS-based spatial information system integrating historical data to map cultural heritage buildings in Palopo - Indrajaya Indrajaya; Amiruddin Akbar Fisu; Zulham A. Hafid; Rakhmawati Natsir; Ahmad Dahlan; Liza Utami Marzaman (Regional Development Information Center, Universitas Sebelas Maret, 2026)
The preservation of cultural heritage buildings in Palopo City faces significant challenges due to rapid urbanization and the absence of robust spatial and historical documentation systems. This study aims to develop a WebGIS-based information system integrated with multi-criteria analysis as a foundation for determining conservation priorities. The research methodology combines a descriptive-qualitative approach with quantitative analysis using Multi-Criteria Decision Analysis (MCDA). The empirical assessment covered 17 cultural heritage buildings in Palopo City, comprising royal and sacred heritage assets, colonial public buildings, military and administrative facilities, and public service buildings. Data were collected through literature review, field surveys, and in-depth interviews with experts, including cultural heritage specialists, architects, and civil engineers, to establish the weights of 17 assessment criteria adapted from international standards and national regulations. Each building’s score was calculated by multiplying the expert-assigned weights with field condition assessments, producing a classification of conservation priorities. MCDA results classified three buildings as high priority, four as medium-high priority, and ten as medium priority. The results were then integrated into a WebGIS platform that interactively displays location maps, historical narratives, architectural attributes, and conservation scores. The system serves not only as a medium for documentation and public education but also as an evidence-based decision-support tool for government, academics, and local communities in preserving the cultural heritage of Palopo City.